Islam as the Core Methodology of International Relations in Islamic Universities in Indonesia - Candra, Rudi; Mubarok, Sofi (Journal of Islamic World and Politics, 2021)
This condition reminds us of the vital role and urgency of developing a methodology of Islamic international relations. In response to this issue, it is necessary to carry out an analysis of the development and application of Islamic international relation methods in Indonesian Universities, in this case, taking the example of three universities: Darussalam University (UNIDA) Gontor, Universitas Muhammadiyah Yogyakarta (UMY), and UIN Sunan Ampel Surabaya. These three universities were chosen because they officially declared the development of Islamization or integration of science in the curriculum of the international relations study program. This study aims to analyze the methodological model of Islamic international relations in three universities to be compared and evaluated for their implementation. This type of research was qualitative descriptive by taking the research settings at UNIDA, UMY, and UIN Sunan Ampel. Data collection techniques were through observation, interviews, and limited discussion. Data analysis utilized an interactive model with a four-component analysis approach: data reduction, data analysis, data clarification, and drawing conclusions carried out actively and interactively with source persons as the primary data sources equipped with several secondary sources. This study found that these three universities used three different methods in embodying the concept of Islam in international relations. UNIDA Gontor has its Islamization project, UMY has Islam as the curriculum characteristic, and UIN Sunan Ampel has the integrated twin tower concept. Although these three models have elementary differences, they have the spirit of developing the internalization of Islamic studies in the study of international relations.